2016
DOI: 10.1246/bcsj.20160267
|View full text |Cite
|
Sign up to set email alerts
|

Exploration into a New Dicarboxylic Acid Derived from Ricinoleic Acid for High-Performance Aluminum Electrolytic Capacitors

Abstract: New dicarboxylic acids were synthesized from ricinoleic acid in 3–8 steps in good overall yields, and they were found to be effective as an electrolyte in aluminum electrolytic capacitors. These types of dicarboxylic acids show good heat-resistance and higher withstand voltage than conventional electrolytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Due to its rigid cyclic structures, it is capable of repairing them on the surface and forming thicker layers so as to achieve the high withstand voltage . Although there are still some issues to be overcome, such as the fact that scintillation is observed from around 550 V, and the solubility in EG is slightly inferior, we concluded that the incorporation of hindered α-substituents led to excellent heat resistance and rigid ring skeletons improved the withstand voltage . The details of the correlation between molecular rigidity and withstand voltage are currently under research.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its rigid cyclic structures, it is capable of repairing them on the surface and forming thicker layers so as to achieve the high withstand voltage . Although there are still some issues to be overcome, such as the fact that scintillation is observed from around 550 V, and the solubility in EG is slightly inferior, we concluded that the incorporation of hindered α-substituents led to excellent heat resistance and rigid ring skeletons improved the withstand voltage . The details of the correlation between molecular rigidity and withstand voltage are currently under research.…”
Section: Results and Discussionmentioning
confidence: 99%
“…On the other hand, we have started to collaborate with NICHICON Corporation to explore new chemical structure of dicarboxylic acids for the development of next-generation AECs. We reported in 2016 that dicarboxylic acids derived from ricinoleic acid showed good heat resistance and withstand higher voltage compared with sebacic acid and 1,6-DDA for AEC (Scheme c) . The solubility of these compounds in EG is, however, still a problem.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidation of methyl ricinoleate was carried out following a reported method with slight modification. [ 20 ] PCC (5.16 g, 24 mmol) was taken in 100 mL of dichloromethane (DCM) and methyl ricinoleate (5g, 16 mmol) was added and the reaction mixture was stirred at room temperature (27 ˚C) for 12 h. After maximum conversion, the mixture was filtered on a celite‐silica bed followed by purification by column chromatography to obtain methyl 12‐oxo‐ cis ‐9‐octadecenoate as oily liquid (4.1 g, 83%). R f : 0.6 in 10% EtOAc in hexane.…”
Section: Methodsmentioning
confidence: 99%
“…After the completion of the reaction, as identified by TLC, the resulting mixture was filtered over Celite and washed well with methanol. The filtrate was collected and the solvent was removed under vacuum to get the pure product …”
Section: Methodsmentioning
confidence: 99%
“…The filtrate was collected and the solvent was removed under vacuum to get the pure product. 36 2.3.2. General Procedure for the Synthesis of Ricinoleic Acid Hydrazide 2a and 2b.…”
Section: Methodsmentioning
confidence: 99%